Relationship Between Disease Stadium And Quality Of Life In Parkinson's Disease Patients In The Neural Polyclinic Of Muhammadiyah University Hospital Malang - Sigit Hari Nursyamsu; Rachmanita Charisma Putri; Risma Karlina Prabawati; Feny Tunjungsari Tunjungsari (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2022)
Parkinson's disease is a chronic progressive neurodegenerative disease of the extrapyramidal system. These symptoms are divided into specific stages based on the severity of the symptoms. Differences in Parkinson's disease severity are linked to the quality of life in Parkinson's disease patients. Demonstrate the relationship between stage and attitude quality in Parkinson's disease patients, Department of Neurology, Muhammadiyah Malang University Hospital. Thirty-seven respondents were obtained from the analytical observations using a crossover design nonrandom objective sampling method. The Hoehn and Yahr Scale for Diagnosing Parkinson's Disease Stage and Parkinson's Disease Questionnaire (PDQ-39) was used to assess the quality of the attitude process in patients with Parkinson's disease during the previous month. The Spearman Rank correction test result is 0.485, which reduces the correction between street and road quality. It is unidirectional because the correlation value is positive, so the higher the ladder, the lower the patient's quality of life. The adjustment between significant variables was 0.002 (α <0.05). This suggests that higher levels determine the quality of patient access. There is a relationship between stage and attitude quality in Parkinson's disease patients in the Department of Neurology, Muhammadiyah Malang University Hospital.